Effect of Surfactant on Morphology and Conductivity of Polyaniline Nanoparticles Prepared in Water/Tetrahydrofuran Solution - Ghafouri Taleghani, Hamidreza; Aleahmad, Mahdi; Eisazadeh, Hossein (Asian Journal of Chemistry, 2010)
Polyaniline nanoparticles were synthesized in a water/tetrahydrofuran solution by using KIO3 as an oxidant in the presence of various surfactants such as hydroxypropylcellulose (HPC), poly(vinyl alcohol) (PVA) and sodium dodecylbenzenesulfonate (DBSNa). The effect of type and concentration of surfactant on the morphology have been investigated. Scanning electron microscopy was used to characterize the morphology of polyaniline. The results indicate that small and spherical nanoparticles can be obtained using PVA (6 g/L). Also better conductivity obtained when DBSNa (6 g/L) was used as surfactant. The chemical structure of products determined by fourier transform infrared spectroscopy (FTIR). The results show that the type of surface active agent affects the intensity of peaks.